L5 RIG-I activation enhances melanoma immunogenicity and improves anti-tumor T cell responses in combination with anti-PD-1 immune checkpoint blocking antibodies. (1st October 2020) - Thier, B; Such, L; Schwamborn, M; Sucker, A; Coch, C; Schadendorf, D; Griewank, K; Trilling, M; Zhao, F; Paschen, A
Abstract : Background: Clinical efficacy of immune checkpoint blocking (ICB) therapy critically relies on the killing of melanoma cells by CD8 + T cells, becoming activated upon recognition of tumor antigens presented by HLA class I (HLA-I) surface molecules. Patient-derived melanoma cells can escape from cytotoxic T cell effector functions by loss of HLA-I surface expression due to the silencing of HLA-I antigen processing and presentation machinery (APM) genes. Material and Methods: Seeking for a strategy to restore HLA-I expression, we transfected melanoma cells obtained from distinct patient metastasis with synthetic short double stranded RNA (3pRNA), an activating ligand of the cytosolic innate pattern recognition receptor RIG-I. 3pRNA-transfected melanoma cells were analyzed for HLA-I surface expression by FACS analysis and gene expression of HLA-I APM components by qPCR. In vivo 3pRNA-transfected tumors were analyzed for HLA-I expression by immunohistochemistry staining. Furthermore, T cell activation after coincubation with 3pRNA-transfected melanoma cells was determined by IFNγ-ELISpot assay. The effect of combined 3pRNA and blocking anti-PD-1 antibody treatment on T cell activation was measured by intracellular cytokine staining and FACS analysis. Results: Activation of RIG-I by 3pRNA increased the expression of HLA-I APM components and strongly enhanced recognition of melanoma cells by autologous CD8 + T cells. Based on these findings, we asked whether the combination of 3pRNA and blocking anti-PD-1 antibodies could improve anti-melanoma T cell responses in an anti-PD-1 non-responder patient model. Indeed, T cell activation by 3pRNA-transfected melanoma cells was significantly increased in the presence of anti-PD-1 antibodies. In line with the enhancement of anti-tumor T cell responses, we found an association of elevated RIG-I mRNA levels with prolonged patient survival in TCGA melanoma samples. Conclusions: In summary, this study demonstrates a beneficial effect of RIG-I activation on antigen presentation and T cell recognition of melanoma cells. Improved T cell responses by combined 3pRNA and anti-PD-1 treatment suggests that combinational therapy could be a strategy to overcome T cell resistance in melanoma. Disclosure Information: B. Thier: None. L. Such: None. M. Schwamborn: None. A. Sucker: None. C. Coch: None. D. Schadendorf: None. K. Griewank: None. M. Trilling: None. F. Zhao: None. A. Paschen: None.